Improving Indonesian Language Learning Outcomes for Elementary School Students through the Use of Picture Media - Nurul Aswar; Hasbi Hasbi; Dodi Ilham (Jurnal Sinestesia, 2022)
This study aims to improve the learning outcomes of Indonesian by using image media in learning. This research is classroom action research (CAR) which consists of two cycles. Each cycle was held for three meetings with the stages of planning, action, observation, and reflection. The data subjects of this study were the fifth-grade students of SD Negeri 3 Kasimpureng in the even semester of the 2021/2022 school year, totaling 23 people. The results showed that the application of image media in learning succeeded in improving students' Indonesian learning outcomes. Based on the test of student learning outcomes carried out in two cycles, it showed that student learning outcomes had increased, from the first cycle the average value was 72 with a percentage of completeness of 65%.